Varicella-Zoster Meningitis With Hypoglycorrhachia in an Immunocompetent Patient Presenting With Disseminated Varicella-Zoster Infection - Sohal, Raman J (Cureus, 2020)
Varicella-zoster virus (VZV) infection is rarely reported in immunocompetent hosts. We report the case of a 40-year-old male who presented with altered mental status. One week prior, he was seen at his outpatient physician’s office for a rash along the lateral right thigh. Erythema of the right gluteal region was noted, but no vesicles were present. He was treated for shingles rash with acyclovir with improvement. After a period of initial improvement in the rash, the patient developed a persistent headache. Given his migraine history, he overlooked the headache. He then developed fever, followed by confusion and was brought to the ED for further evaluation. CT head was unremarkable. Lumbar puncture revealed aseptic meningitis. This case highlights the unusual presentation of disseminated VZV infection in an immunocompetent host. It stresses the importance of maintaining high suspicion for disseminated VZV infection despite the patient being immunocompetent.